Agricultural Societies of Ukrainian Provinces in Russian Empire: the Formation of Network and Experience (1861–1914) - Lysenko, M.S. (My University, 2015)
Стаття присвячена діяльності сільськогосподарських товариств українських губерній Російської імперії у період з 1861 р. по 1914 р. На основі архівних матеріалів та друкованих джерел автор вивчив причини виникнення, динаміку чисельності аграрних об’єднань. Охарактеризовані різні типи аграрних організацій за масштабами їхньої роботи (центральні, обласні, губернські, повітові та сільські) і спеціалізації (землеробські, тваринницькі, садівничі та ін.). Сільськогосподарські товариства Правобережжя, Лівобережжя та Півдня України мали свою специфіку у методах роботи з населенням, засобах господарювання, науковій і комерційній базі. Після початку I Світової війни активність вищезгаданих товариств зменшилась. Сільськогосподарські організації зробили значний внесок у модернізацію аграрного сектора українських губерній Російської держави. Статья посвящена деятельности сельскохозяйственных обществ украинских губерний Российской империи в период с 1861 г. по 1914 г. На основе архивных материалов и опубликованных источников автор изучил причины возникновения, динамику численности аграрных объединений. Охарактеризованы разные типы аграрных организаций по масштабу их работы (центральные, областные, губернские, уездные и сельские) и специализации (земледельческие, животноводческие, садоводческие и т. п.). Сельскохозяйственные общества Правобережья, Левобережья и Южной Украины имели свою специфику в методах работы с населением, способах хозяйствования, научной и коммерческой основе. После начала I Мировой войны активность данных обществ снизилась. Сельскохозяйственные организации внесли вклад в модернизацию аграрного сектора украинских губерний Российского государства. The article deals with the activities of agricultural societies in the Ukrainian provinces of the Russian Empire in the period from 1861 to 1914. The author has studied the reasons of occurrence, population dynamics of agricultural associations based on archival materials and published sources. Different types of agrarian organization on the scale of their work (central, regional, provincial, district and village) and specialization (agricultural, livestock, gardening, etc.) were characterized. Agricultural societies of the Right Bank, Left Bank, and Southern Ukraine had its own specificity in the methods of work with the inhabitants, methods of management, scientific and commercial basis. The activity of these companies decreased after the start of World War I. Agricultural organizations have contributed to the modernization of the agricultural sector of Ukrainian provinces of the Russian state.
Keywords: сільськогосподарські товариства; українські губернії; Російська імперія; сільське господарство; сельскохозяйственные общества; украинские губернии; Российская империя; сельское хозяйство; agricultural societies; the Ukrainian provinces; Russian Empire; agriculture